THE The power and both sides - Rojo Martínez, Alejandro (2021)
Today should be remembered that the quality of a republic, society and politics that support is in the division of powers. So figure in our past constitutions, and in the currentThe republic and democracy do not refer only to a form of the state that sovereignty belongs to all and the division of powers is recognized in the Supreme Charter. It is also a way of governing, and assumes that the rulers at national level, legislators, political parties, authorities of any kind, but also the citizens and organizations they form, are guided primarily by the collective good and not by self-interest.Democracy accepts private interests and goals of individuals and groups, but making them see that there is also a common good that precautionary and that those same private goals would not be achieved outside possibility of living together. Aristotle's exercise of power condemns the confusion between private good and the public good and not to mention the appropriation of this by that.Known these parameters corresponds democratic government to address national problems and proceed with diligence and determination in his solution. Postpone or limit it will pay dearly. The republic, democracy and the exercise of power play a decisive role in the desired recovery of nations that pride themselves on their democracy as a form of government.